The Flow Inventory for Student: Validation of the LIS - Yuwanto, Listyo (ANIMA Indonesian Psychological Journal, 2011)
Limitations of the academic flow instrument developed so far became the basis of this research.The validated academic flow instrument is the the FLow Inventory for Student (LIS), consisting12 items representing absorption, enjoyment, and intrinsic motivation aspects. The LIS aspectswere based on the aspects of Work-reLated Flow Inventory (WOLF), developed by Bakker(2008). The validation was based on content evidence and internal structural analysis, while thereliability refers to alpha Cronbach internal consistency. Undergraduate students (N=306) wereparticipating through incidental sampling. Exploratory factor analysis results reveal that LISconsist of 10 items containing four items of absorption, three items of enjoyment, and threeitems of intrinsic motivation. These items have factor loading > .4 with no cross loadingindication. The reliability score using alpha Cronbach internal consistency is > .6. The resultsare discussed further. Keterbatasan alat ukur flow akademik yang dikembangkan selama ini mendasari penelitianvalidasi alat ukur flow akademik. Alat ukur flow akademik yang diuji validasi dinamakan TheFLow Inventory for Student (LIS), yang terdiri atas 12 butir mewakili aspek absorption, enjoy-ment, dan intrinsic motivation. Aspek-aspek LIS didasarkan pada aspek alat ukur Work-reLatedFlow Inventory (WOLF) yang dikembangkan Bakker (2008). Validasi meliputi pengujian validi-tas berdasarkan bukti content dan internal structural analysis serta reliabilitas mengacu padainternal consistency alpha cronbach. Subjek penelitian berjumlah 306 mahasiswa yang diperolehmelalui incidental sampling. Hasil uji analisis faktor exploratory menunjukkan LIS terdiri atas10 butir dengan komposisi empat butir absorption, tiga butir enjoyment, dan tiga butir intrinsicmotivation. Butir-butir tersebut memiliki factor loading > 0,4 dan tidak ada indikasi crossloading. Reliabilitas internal consistency alpha cronbach LIS > .6. Hasil penelitian didiskusikanlebih lanjut.